Weed Management in Spring Seeded Barley, Oats, and Wheat with Prosulfuron - Nader Soltani; Lynette R. Brown; Todd Cowan; Peter H. Sikkema (International Journal of Agronomy)
A limited number of preplant (PP) herbicides are available for spring seeded cereals in Ontario. Six field trials were conducted at the Huron Research Station, Exeter, Ontario, over a two-year period (Exeter, 2010 and 2011) to evaluate glyphosate, prosulfuron, and glyphosate plus prosulfuron applied PP for weed management in spring seeded no-till barley, oats, and wheat. There was no injury in barley, oats, and wheat with glyphosate, prosulfuron, and glyphosate plus prosulfuron applied preplant at the rates evaluated at 1, 2, and 4 weeks after crop emergence. Prosulfuron provided 49–99% control of AMBEL, 28% or less control of CONAR, 31–94% control of POLCO, 49–98% control of SINAR, and 46–79% control of SONAR. Prosulfuron in combination with glyphosate provided 73–98% control of AMBEL, less than 43% control of CONAR, 39–94% control of POLCO, 63–98% control of SINAR, and 60–85% control of SONAR. Prosulfuron reduced density of AMBEL 76% and SINAR 93% but had no significant effect on density of CONAR, POLCO, or SONAR. Prosulfuron in combination with glyphosate reduced biomass of AMBEL as much as 96% and SINAR 98% but had no significant effect on biomass of CONAR, POLCO, or SONAR. Yield of barley, oats, and wheat was not affected with glyphosate, prosulfuron, and glyphosate plus prosulfuron at the rates evaluated.